The patient musician: a qualitative investigation of professional classical musicians who previously suffered from depression - Michaela Korte; Deniz Cerci; Roman Wehry; Renee Timmers; Victoria J. Williamson (BMC Public Health)
Abstract Background Music students are more vulnerable to depression than their peers in many other academic fields. Contributing factors include early specialization and social isolation resulting from long hours of practice, the prevalence of chronic pain and the challenges associated with developing a coherent identity within the context of an inherently competitive field. Moreover, the culture around music seems to reward suffering at times, which may impede seeking professional medical assistance. Method Seven professional classical musicians participated in a written semi-structured interview. This study aimed to gain insight into the experiences of classical musicians who have been medically diagnosed with depression at some point during their studies and in their subsequent careers. The objective was to identify the specific challenges faced by musicians and the (effective) strategies employed. Furthermore, the focus was on enhancing awareness of the existing resources and developing strategies for further improvement. Results The findings indicated that all participants were embedded within a robust social support system that facilitated their ability to seek medical assistance. They received a standard medical treatment, which included cognitive-behavioral therapy with or without medication. Financial difficulties, the impact of an inability to work, and external expectations were among the most prevalent challenges. Distinctive challenges specific to musicians during depression included a decline in their creative output, a loss of voice, heightened anxiety, and difficulties to engage with emotions. Participants indicated that their strategies for enhancing their health were largely based on their individual resourcefulness and not necessarily a direct result of their formal education. Conclusion The findings indicate the necessity of integrating a positive approach to (performance) anxiety, establishing secure environments for vulnerable students beyond their academic settings, and enhancing students’ awareness of available (medical) standard multidisciplinary treatments. The emergence of a specialized, board-certified field of musicians’ medicine within the medical field is a promising development that could provide support to musicians and facilitate their long-term career prospects.